Population Movement Patterns and Spatial Distribution of Dengue Hemorrhagic Fever Incidence in Makassar City - Andi Muhammad Rezky Anugrah AR; Ruslan La Ane; Owildan Wisudawan; Rosa Devitha Ayu (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health issue in Makassar City characterized by fluctuating transmission patterns. High population mobility and urban density are suspected contributors to the spatial distribution of the disease, yet studies integrating daily movement dynamics with DHF incidence remain limited. This study aims to analyze population movement patterns (motivation, frequency, distance) and their relationship to the distribution of DHF incidence in Makassar City. This cross-sectional observational study employed a spatial-temporal approach. A total of 111 respondents from nine urban villages (kelurahan) were selected via stratified random sampling based on endemicity levels. Associations between DHF history and mobility variables were tested using The Chi-Square (movement motivation) and The Wilcoxon tests (movement frequency and distance).  The results showed no statistically significant association between DHF history and movement motivation (Chi-square, p = 0.949), frequency (Wilcoxon, p = 0.435), or distance (Wilcoxon, p = 0.617). However, spatial analysis identified active population movement from high-endemicity to low-endemicity areas, potentially facilitating cryptic viral transmission through daily connectivity. Furthermore, land use analysis revealed that high-endemic areas are dominated by dense settlements with limited green open space (<10%). In conclusion, while individual movement variables show no statistical association with DHF history, the spatial connectivity suggests the need for cross-boundary dengue control. Priority should be given to surveillance and vector control at high-mobility activity hubs (e.g., schools, workplaces, and transit-linked areas) to disrupt transmission chains.